Ethnicity, Smoking Status, and Preterm Birth as Predictors of Maternal Locus of Control. (April 2015) - Ashford, Kristin B.; Rayens, Mary Kay
A woman's psychological health can affect prenatal behaviors. The purpose of this study was to examine the relationship between maternal beliefs, prenatal behaviors, and preterm birth (PTB) in a multiethnic population. This was a planned secondary analysis of a cross-sectional trial of postpartum women with singleton gestation. In all, 210 participants were given the Fetal Health Locus of Control (FHLC) scale to measure three primary maternal beliefs that influenced their prenatal behaviors (Internal Control, Chance, Powerful Others). Women who experienced preterm delivery and those who smoked during pregnancy scored the Chance category significantly higher than those who delivered term infants ( p = .05; p = .004, respectively). This suggests those who smoked during pregnancy had a greater degree of belief that Chance influenced their infant's health status. Cultural differences also emerged specific to the impact of health care providers on PTB; with Hispanic women scoring Powerful Others the highest among the groups ( p = .02). Nurses can plan a critical role in identifying at-risk women (smoking, strong Chance beliefs) while providing a clear message that taking action and modifying high-risk behaviors can reduce risk for adverse pregnancy outcome.